Robust capital regulation - Viral Acharya; Hamid Mehran; Til Schuermann; Anjan Thakor (Federal Reserve Bank of New York, 2011)
Banks' leverage choices represent a delicate balancing act. Credit discipline argues for more leverage, while balance-sheet opacity and ease of asset substitution argue for less. Meanwhile, regulatory safety nets promote ex post financial stability, but also create perverse incentives for banks to engage in correlated asset choices and to hold little equity capital. As a way to cope with these distorted incentives, we outline a two-tier capital framework for banks. The first tier is a regular core capital requirement that helps deter excessive risk-taking incentives. The second tier, a novel aspect of our framework, is a special capital account that limits risk taking but preserves creditors' monitoring incentives.
Keywords: G12; G21; 330; capital requirements; leverage; systemic risk; Bank; Kapitalstruktur; Fremdkapital; Risiko; Bankenaufsicht